Efficacy and safety outcomes of fractional flow reserve in guiding clinical therapy of non-ST-segment elevation myocardial infarction compared with angiography alone in elderly Chinese patients - Zhang Z (Dove Medical Press, 2016)
Zhao Zhang,* Ke Li,* Jinwen Tian Department of Cardiology, Chinese People’s Liberation Army General Hospital and Hainan Branch, Sanya, People’s Republic of China *These authors contributed equally to this work Objective: Fractional flow reserve (FFR) is an innovative method for evaluating the physiological significance of a coronary stenosis, but its validity is less certain in patients with non-ST-segment elevation myocardial infarction (NSTEMI). It is important to assess whether FFR is effective and safe in patients, especially elderly Chinese patients, with NSTEMI. As the first one in China, the purpose of this study was to establish the efficacy and safety outcomes of FFR in guiding clinical therapy of NSTEMI compared with angiography alone in elderly Chinese patients. Patients and methods: This prospective randomized controlled study included 220 patients with NSTEMI older than 65 years. Patients were assigned in a ratio of 1:1 to the FFR-guided group and the angiography-guided group, and their outcomes were evaluated after 1 year of follow-up. Results: The mean age of the patients was 70±3.6 years, and 69.6% were men. Baseline characteristics of the patients had no differences between the two groups (P>0.05 for all). No differences in adverse events, including major adverse cardiovascular event, major adverse cardiovascular and cerebrovascular event, cardiovascular death, nonfatal myocardial infarction, heart failure, stroke, transient ischemic attack, all-cause mortality, contrast nephropathy, and major bleeding, was observed between the two groups during the follow-up (P>0.05 for all). The number of patients receiving medical therapy alone in the FFR-guided group was significantly more than that in the angiography-guided group (P<0.05). Conclusion: Compared with angiography-guided standard therapy, FFR reduced the application of percutaneous coronary intervention and obtained similar outcomes, demonstrating that FFR was effective and safe in guiding clinical therapy of NSTEMI in elderly Chinese patients. Keywords: elderly Chinese patients, fractional flow reserve, non-ST-segment elevation myocardial infarction